Mimosa pudica : experiment of thermal stimulation of plant movements - Ting, Hui Ying (2016)
Mimosa pudica, which is also known as sensitive plant or touch-me-not plant, got its name due to the closing of the leaves when in contact with external stimulation and reopening after some time. Not only that, the leaves will close at night and open in the days. These mechanisms have caught researchers’ attention and many researches had been done to find out the reasons behind it to help in the understanding of the biology of plant and how it can be helpful in the different aspects of the industries like biological, medical, engineering, etc. It is important to know about the basics of the mimosa pudica before coming out with new premises which will help in a better understanding of it. Thus, a literature review will be written to uncover all the researches done on mimosa plants before getting on with the main scope of this report. In this report, a study on the fatigue effects of the mimosa plant by studying the response time uses continuous stimulation of mechanical stimulation at atmospheric temperature and thermal stimulation using different temperatures. The results concluded that the higher the temperature, the time taken for the leaves to close is shorter but longer during the reopening. This study will help to better apprehend the mechanism and biology behind mimosa pudica.